Density, flash point, viscosity, and heating value of waste cooking biodiesel (B20) with bioadditive essential oil (lemon, lemongrass, eucalyptus). (July 2020) - Permanasari, A A; Sukarni, S; Wulandari, R; Puspitasari, P; Mauludi, M N; Ramadani, R
Abstract: This research is motivated by the decreasing of fossil fuels in the earth while the level of consumption of fossil fuels is getting higher from year to year, so the need for alternative fuels increases, one of which is biodiesel. The existence of studies in preparing biodiesel as an alternative fuel is essential. This study aimed to determine the effect of bioadditive essential oils (lemon, lemongrass, and eucalyptus) on biodiesel fuels' thermophysical properties. The method used in this study is using esterification and transesterification step for making biodiesel. The character of biodiesel can be recognized by testing the physicochemical properties which consist of kinematic viscosity, density, flash point, and low heating value tests. The results show that the density of all samples is not significantly different in value. Increased density occurs in each sample due to the higher concentration of essential oils. As the concentration of essential oil increases, flashpoint tends to decrease. Low heating value tends to decrease with the increase concentration of essential oil. Kinematic viscosity has a value that tends to decrease with the addition of essential oil concentrations.